A kind of anti-aging sound insulation material and preparation method thereof
By mixed foaming materials such as phosphor glycol, 1,4-butanol, deodorded water, liquid paraffin, polymerized polytyornes, modified polymoh nanotoxide, and hydrogen-containing silicone oil, preparation of anti-aging sound insulation materials, The problem of existing sound insulation materials in outdoor aging degradation has been solved, and better anti -aging, flame retardant and sound insulation performance is achieved.
Patent Information
- Application Number
- CN202410425635.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-10
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-04-10
AI Technical Summary
Existing sound insulation materials are susceptible to ultraviolet rays, temperature, humidity and pollutants when exposed to outdoor environments for a long time, resulting in aging and degradation, yellowing, surface cracking, mechanical properties, and shortening service life.
Anti-aging sound insulation materials are prepared by mixing and foaming materials such as phosphorus-containing glycol, 1,4-butanediol, deionized water, liquid paraffin, polymerized polyisocyanate, modified porous nano-titanium dioxide microspheres and hydrogen-containing silicone oil.
Improve the anti -aging performance, flame retardant performance and sound insulation performance of anti -aging sound insulation materials, extend the service life, and provide a stable protective layer at high temperature.
Smart Images

Figure BDA0004783911780000031 
Figure BDA0004783911780000041 
Figure BDA0004783911780000042
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sound insulation materials, in particular to an anti-aging sound insulation material and a preparation method thereof. Background Art
[0002] With the development of modern industry and information, noise pollution has become more and more prominent. Noise not only hinders people's rest and sleep, interferes with language conversation and daily social life, but also seriously affects people's physical and mental health, quality of life, and even the life of various equipment in life. Sound insulation is to isolate, separate and separate the noise transmitted in the air, including sound absorption and reflection. The main function of sound insulation materials is to reflect and absorb sound waves. Sound insulation and noise reduction materials can be divided into porous materials, plate materials, molded ceiling sound absorbing panels, membrane materials, and flexible materials. Different materials have different reflection effects on sound waves due to their different surface morphologies. When sound waves pass through different sound insulation materials, the ratio of the reflected component to the absorbed component will also be different.
[0003] Polyurethane can be used to prepare foam, fiber, rubber and elastomer. According to the open-cell situation of the foam, it can be divided into hard and soft. The open-cell structure is soft polyurethane foam, which has low relative density, high specific strength, good chemical resistance, resilience, and mechanical properties, and has excellent heat insulation, sound insulation, shock resistance and anti-toxic properties. Due to its high viscoelasticity, it has a good damping effect, can effectively reduce the propagation of noise, and is widely used in sound insulation materials. However, long-term exposure to the outdoors will be affected by ultraviolet rays, temperature, humidity, ozone, and pollutants in the atmosphere, resulting in serious aging and degradation, causing the product color to turn yellow, the surface to crack, and the mechanical properties to seriously decrease, shortening its service life. Therefore, the present invention prepares an anti-aging sound insulation material with excellent anti-aging performance, flame retardant performance and sound insulation performance. Summary of the invention
[0004] The purpose of the present invention is to provide an anti-aging sound insulation material and a preparation method thereof, so as to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] An anti-aging sound insulation material is characterized in that the anti-aging sound insulation material is obtained by foaming a mixture of phosphorus-containing diol, 1,4-butanediol, deionized water, liquid paraffin, polymerized polyisocyanate, modified porous nano titanium dioxide microspheres and hydrogen-containing silicone oil.
[0007] As an optimization, the liquid paraffin model is industrial grade and comes from Shandong Yaoda New Materials Co., Ltd.
[0008] As an optimization, the polymeric polyisocyanate model is 101-68-8, which comes from Nantong Runfeng Petrochemical Co., Ltd.
[0009] As an optimization, the hydrogen-containing silicone oil model is MY202, which comes from Anhui Mingyi Silicon Industry Co., Ltd.
[0010] As an optimization, the phosphorus-containing diol is prepared by reacting allyl phosphine dichloride and polyethylene glycol.
[0011] As an optimization, the polyethylene glycol model is PEG800, which comes from Jinan Xinke Chemical Co., Ltd.
[0012] As an optimization, the modified porous nano titanium dioxide microspheres are obtained by coating tetrabutyl titanate on a polystyrene microsphere template and then sintering, and then reacting with hydroxymethyltriethoxysilane and 2-(5-chloro-2H-benzotriazole-2-yl)-6-(2-methyl-2-propyl)-4-vinylphenol in sequence.
[0013] A method for preparing an anti-aging sound insulation material comprises the following preparation steps:
[0014] (1) The polystyrene microsphere template emulsion and anhydrous ethanol are mixed in a mass ratio of 1: (99-101), stirred at 75-85° C. and 100-200 rpm for 25-35 min, tetrabutyl titanate in an amount of 0.1-0.2 times the mass of the polystyrene microsphere template emulsion is added, stirring is continued for 25-35 min, ammonia water in an amount of 7-9 times the mass of the polystyrene microsphere template emulsion with a mass fraction of 26-28% is added at a uniform rate within 3-5 h, stirring is continued for 1-3 h, centrifuged, washed with deionized water for 3-5 times, dried at 55-65° C. for 4-6 h, ground for 10-20 min, transferred into a muffle furnace and ablated at 450-550° C. for 1-3 h, and naturally cooled to room temperature to obtain porous nano-titanium dioxide microspheres;
[0015] (2) The porous nano-titanium dioxide microspheres and the ethanol solution with a mass fraction of 97-98% are mixed at a mass ratio of 1:(15-17), ultrasonically dispersed for 25-35 minutes, 2-4 times the mass of the porous nano-titanium dioxide microspheres are added with hydroxymethyltriethoxysilane, and ultrasonic dispersion is continued for 25-35 minutes. The temperature is raised to 55-65°C, stirred at 150-250 rpm for 2-4 hours, and then centrifuged. The solution is washed with anhydrous ethanol for 3-5 times, and dried at 45-55°C for 47-49 hours to obtain pre-modified porous nano-titanium dioxide microspheres; the pre-modified porous nano-titanium dioxide microspheres, sodium hydride and N,N-dimethylformamide are mixed at a mass ratio of 1:(0.05-0.07):(9-11) , stirring at 6-8°C and 100-200rpm for 10-20min, adding 2-(5-chloro-2H-benzotriazole-2-yl)-6-(2-methyl-2-propyl)-4-vinylphenol in an amount of 1.6-1.8 times the mass of the pre-modified porous nano-titanium dioxide microspheres, continuing stirring for 2-3h, naturally returning to room temperature, quenching with deionized water at 3-5°C, adding ethyl acetate in an amount of 30-40 times the mass of the pre-modified porous nano-titanium dioxide microspheres to extract the liquid, washing with a sodium chloride solution with a mass fraction of 26-27% and deionized water for 3-5 times respectively, and then drying with anhydrous sodium sulfate for 1-2h, distilling under reduced pressure and purifying with a silica gel chromatography column to obtain modified porous nano-titanium dioxide microspheres;
[0016] (3) mixing allyl phosphine dichloride and n-hexane in a mass ratio of 1:(3-4), stirring at 20-30° C. and 100-200 rpm for 10-20 min to obtain a reaction solution; mixing polyethylene glycol and tetrahydrofuran in a mass ratio of 1:(2-3), stirring at 20-30° C. and 400-500 rpm for 10-20 min, heating to 40-50° C., adding the reaction solution at a uniform rate while stirring within 30-40 min, wherein the ratio of the molar amount of allyl phosphine dichloride in the reaction solution to the molar amount of hydroxyl groups in the polyethylene glycol is 1:4, standing for 0.5-1.5 h after the addition, and rotary evaporating to obtain a phosphorus-containing diol;
[0017] (4) Phosphorus-containing diol, triethanolamine, 1,4-butanediol, deionized water, liquid paraffin and modified porous nano-titanium dioxide microspheres are mixed in a mass ratio of 1: (0.1-0.2): (1.2-1.6): (0.1-0.3): (0.6-0.7): (1.2-1.4), stirred at 1500-2500 r / min for 1-3 min, added with 0.6-0.8 times the mass of phosphorus-containing diol melt-polymerized polyisocyanate, continued stirring for 5-15 s, added with 2-3 times the mass of phosphorus-containing diol hydrogenated silicone oil and 0.01-0.02 times the mass of phosphorus-containing diol chloroplatinic acid, continued stirring for 1-3 min, poured into a mold coated with dimethyl silicone oil, foamed at 20-30°C for 5-15 min, and allowed to stand at 65-75°C for 23-25 h to obtain an anti-aging sound insulation material.
[0018] As an optimization, the polystyrene microsphere template emulsion in step (1) is prepared by mixing polyvinyl pyrrolidone and deionized water in a mass ratio of 1:(48-52), stirring at 20-30° C. and 200-400 rpm for 25-35 min, adding styrene in an amount 4-6 times the mass of polyvinyl pyrrolidone, continuing to stir for 10-20 min at 65-75° C. in a nitrogen atmosphere, adding potassium persulfate in an amount 0.07-0.08 times the mass of polyvinyl pyrrolidone, and continuing to stir for 23-25 h.
[0019] As an optimization, the reaction equation of the pre-modified porous nano-titanium dioxide microspheres in step (2) is:
[0020]
[0021] As an optimization, the reaction equation for modifying the porous nano-titanium dioxide microspheres in step (2) is:
[0022]
[0023] As an optimization, the reaction equation of the phosphorus-containing diol in step (3) is:
[0024]
[0025] As an optimization, the melt-polymerized polyisocyanate in step (4) is obtained by melting the polymerized polyisocyanate at 75-85° C. for 6-8 hours.
[0026] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0027] When preparing the anti-aging sound insulation material, the present invention comprises the following steps: coating tetrabutyl titanate on a polystyrene microsphere template and then sintering to obtain porous nano titanium dioxide microspheres; then reacting the porous nano titanium dioxide microspheres with hydroxymethyltriethoxysilane and 2-(5-chloro-2H-benzotriazole-2-yl)-6-(2-methyl-2-propyl)-4-vinylphenol in sequence to obtain modified porous nano titanium dioxide microspheres; reacting allyl phosphine dichloride and polyethylene glycol to obtain phosphorus-containing diol; then mixing the phosphorus-containing diol, 1,4-butanediol, deionized water, liquid paraffin, melt-polymerized polyisocyanate, modified porous nano titanium dioxide microspheres and hydrogen-containing silicone oil and foaming to obtain the anti-aging sound insulation material.
[0028] Firstly, tetrabutyl titanate is coated on a polystyrene microsphere template and then sintered to obtain porous nano titanium dioxide microspheres; then the porous nano titanium dioxide microspheres are reacted with hydroxymethyltriethoxysilane and 2-(5-chloro-2H-benzotriazole-2-yl)-6-(2-methyl-2-propyl)-4-vinylphenol in sequence to obtain modified porous nano titanium dioxide microspheres; the polystyrene microsphere template is coated with tetrabutyl titanate to prepare porous nano titanium dioxide microspheres with high porosity, thereby increasing the specific surface area and the The scattering and diffraction of ultraviolet light and the reflection and scattering of sound waves improve the anti-aging and sound insulation properties of the anti-aging sound insulation materials; the grafting of hydroxymethyltriethoxysilane and 2-(5-chloro-2H-benzotriazole-2-yl)-6-(2-methyl-2-propyl)-4-vinylphenol improves the dispersibility of porous nano-titanium dioxide microspheres. At the same time, the introduction of benzotriazole structure and hindered phenol structure absorbs ultraviolet rays and captures active free radicals, further enhancing the anti-aging properties of the anti-aging sound insulation materials.
[0029] Secondly, allyl phosphine dichloride and polyethylene glycol are reacted to obtain phosphorus-containing diol; phosphorus-containing diol, 1,4-butanediol, deionized water, liquid paraffin, melt-polymerized polyisocyanate, modified porous nano-titanium dioxide microspheres and hydrogen-containing silicone oil are mixed and foamed to prepare anti-aging sound insulation materials; allyl phosphine dichloride and polyethylene glycol are reacted to introduce phosphorus element, which can generate an inert carbon layer during combustion to isolate the combustion products and improve the flame retardant properties of the anti-aging sound insulation materials; hydrogen-containing silicone oil can undergo addition reaction with double bonds on allyl phosphine dichloride and modified porous nano-titanium dioxide microspheres to enhance the cross-linking effect between materials and improve stability; at the same time, hydrogen-containing silicone oil can decompose at high temperature to generate a silicon oxide layer to form a stable protective layer, which further improves the flame retardant properties of the anti-aging sound insulation materials. DETAILED DESCRIPTION
[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0031] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the test methods of various indicators of the anti-aging sound insulation materials prepared in the following examples are as follows:
[0032] Sound insulation performance: The anti-aging sound insulation materials obtained in each embodiment and the comparative example were tested for sound absorption coefficient at 1000 Hz according to GB / T18696.
[0033] Flame retardant properties: The anti-aging sound insulation materials obtained in each embodiment and the comparative example were tested for limiting oxygen index according to GB / T2406.
[0034] Anti-aging performance: The anti-aging sound insulation materials obtained in each embodiment and the comparative example were cut into two 30mm×30mm×30mm specimens by a cutting machine; Thermal oxygen aging: The compressive strength σc0 of the specimen when the deformation amount was 66.6% was tested at a compression speed of 10mm / min, and the specimen was aged at 120°C for 7 days, and the compressive strength σc1 was measured again, and the compressive strength retention rate was calculated as σc1 / σc0*100%, and the thermal oxygen aging resistance was judged; Light oxygen aging: The tensile strength σ0 was tested according to GB / T6344 at a wavelength of 420nm and an irradiance of 1.10W / m 2 Under ultraviolet light conditions, expose at 63°C for 3.8 hours, move into a dark environment at 43°C for 1 hour, cycle 100 times, test the tensile strength σ1 again, and calculate the tensile strength retention rate = σc1 / σc0*100%.
[0035] Example 1
[0036] A method for preparing an anti-aging sound insulation material, the method for preparing an anti-aging sound insulation material comprising the following preparation steps:
[0037] (1) The polystyrene microsphere template emulsion and anhydrous ethanol were mixed at a mass ratio of 1:99, stirred at 75°C and 100 rpm for 35 minutes, tetrabutyl titanate was added at a mass of 0.1 times the mass of the polystyrene microsphere template emulsion, and the stirring was continued for 35 minutes. Ammonia water with a mass fraction of 26% and a mass fraction of 7 times the mass of the polystyrene microsphere template emulsion was added at a uniform speed within 3 hours, and the mixture was stirred for 3 hours and then centrifuged. The mixture was washed with deionized water for 3 times, dried at 55°C for 6 hours, and then ground for 10 minutes. The mixture was transferred into a muffle furnace and ablated at 450°C for 3 hours, and naturally cooled to room temperature to obtain porous nano-titanium dioxide microspheres;
[0038] (2) The porous nano-titanium dioxide microspheres and the ethanol solution with a mass fraction of 97% were mixed in a mass ratio of 1:15, ultrasonically dispersed for 25 minutes, hydroxymethyltriethoxysilane with a mass fraction of twice that of the porous nano-titanium dioxide microspheres was added, and ultrasonic dispersion was continued for 25 minutes. The temperature was raised to 55°C, stirred at 150 rpm for 4 hours, and then centrifuged. The solution was washed with anhydrous ethanol for 3 times and dried at 45°C for 49 hours to obtain pre-modified porous nano-titanium dioxide microspheres. The pre-modified porous nano-titanium dioxide microspheres, sodium hydride and N,N-dimethylformamide were mixed in a mass ratio of 1:0.05:9, and heated at 6°C and 200r / min for 3 hours. pm, stirring for 20 min, adding 2-(5-chloro-2H-benzotriazole-2-yl)-6-(2-methyl-2-propyl)-4-vinylphenol in an amount of 1.6 times the mass of the pre-modified porous nano-titanium dioxide microspheres, continuing stirring for 3 h, naturally returning to room temperature, quenching with deionized water at 3°C, adding ethyl acetate in an amount of 30 times the mass of the pre-modified porous nano-titanium dioxide microspheres to extract the separated liquid, washing with a sodium chloride solution with a mass fraction of 26% and deionized water for 3 times respectively, and then drying with anhydrous sodium sulfate for 1 h, and purifying with a silica gel chromatography column after reduced pressure distillation to obtain modified porous nano-titanium dioxide microspheres;
[0039] (3) Allyl phosphine dichloride and n-hexane are mixed in a mass ratio of 1:3, and stirred at 20° C. and 100 rpm for 20 min to obtain a reaction solution; polyethylene glycol and tetrahydrofuran are mixed in a mass ratio of 1:2, and stirred at 20° C. and 400 rpm for 20 min, and the temperature is raised to 40° C., and the reaction solution is added at a uniform rate within 30 min while stirring, and the ratio of the molar amount of allyl phosphine dichloride in the reaction solution to the molar amount of hydroxyl groups in the polyethylene glycol is 1:4. After the addition, the mixture is allowed to stand for 0.5 h, and rotary evaporated to obtain a phosphorus-containing diol;
[0040] (4) Phosphorus-containing diol, triethanolamine, 1,4-butanediol, deionized water, liquid paraffin and modified porous nano-titanium dioxide microspheres were mixed in a mass ratio of 1:0.1:1.2:0.1:0.6:1.2, stirred at 1500 r / min for 3 min, added with 0.6 times the mass of the phosphorus-containing diol melt-polymerized polyisocyanate, continued stirring for 15 s, added with 2 times the mass of the phosphorus-containing diol hydrogenated silicone oil and 0.01 times the mass of the phosphorus-containing diol chloroplatinic acid, continued stirring for 3 min, poured into a mold coated with dimethyl silicone oil, foamed at 20°C for 15 min, and allowed to stand at 65°C for 25 h to obtain an anti-aging sound insulation material.
[0041] Example 2
[0042] A method for preparing an anti-aging sound insulation material, the method for preparing an anti-aging sound insulation material comprising the following preparation steps:
[0043] (1) The polystyrene microsphere template emulsion and anhydrous ethanol were mixed at a mass ratio of 1:100, stirred at 80°C and 150 rpm for 30 min, tetrabutyl titanate was added at a mass of 0.15 times the mass of the polystyrene microsphere template emulsion, and the stirring was continued for 30 min. Ammonia water with a mass fraction of 27% and a mass fraction of 8 times the mass of the polystyrene microsphere template emulsion was added at a uniform speed within 4 h, and the mixture was stirred for 2 h and then centrifuged. The mixture was washed with deionized water for 4 times, dried at 60°C for 5 h, and then ground for 15 min. The mixture was transferred into a muffle furnace and ablated at 500°C for 2 h, and naturally cooled to room temperature to obtain porous nano-titanium dioxide microspheres;
[0044] (2) The porous nano-titanium dioxide microspheres and the ethanol solution with a mass fraction of 97.5% were mixed at a mass ratio of 1:16, and ultrasonic dispersion was performed for 30 minutes. Hydroxymethyltriethoxysilane with a mass fraction of 3 times that of the porous nano-titanium dioxide microspheres was added, and ultrasonic dispersion was continued for 30 minutes. The temperature was raised to 60°C, stirred at 175 rpm for 3 hours, and then centrifuged. The solution was washed with anhydrous ethanol for 4 times, and dried at 50°C for 48 hours to obtain pre-modified porous nano-titanium dioxide microspheres. The pre-modified porous nano-titanium dioxide microspheres, sodium hydride and N,N-dimethylformamide were mixed at a mass ratio of 1:0.06:10, and heated at 7°C and 150 rpm for 48 hours. Stir for 15 min, add 2-(5-chloro-2H-benzotriazole-2-yl)-6-(2-methyl-2-propyl)-4-vinylphenol in an amount of 1.7 times the mass of the pre-modified porous nano-titanium dioxide microspheres, continue stirring for 2.5 h, naturally return to room temperature, quench with deionized water at 4°C, add ethyl acetate in an amount of 35 times the mass of the pre-modified porous nano-titanium dioxide microspheres to extract the separated liquid, wash with a sodium chloride solution with a mass fraction of 26.5% and deionized water for 4 times respectively, and then dry with anhydrous sodium sulfate for 1.5 h, and purify with a silica gel chromatography column after reduced pressure distillation to obtain modified porous nano-titanium dioxide microspheres;
[0045] (3) Allyl phosphine dichloride and n-hexane are mixed in a mass ratio of 1:3.5, and stirred at 25° C. and 150 rpm for 15 minutes to obtain a reaction solution; polyethylene glycol and tetrahydrofuran are mixed in a mass ratio of 1:2.5, and stirred at 25° C. and 450 rpm for 15 minutes, and the temperature is raised to 45° C., and the reaction solution is added at a uniform rate within 35 minutes while stirring, and the ratio of the molar amount of allyl phosphine dichloride in the reaction solution to the molar amount of hydroxyl groups in the polyethylene glycol is 1:4. After the addition, the mixture is allowed to stand for 1 hour, and rotary evaporated to obtain a phosphorus-containing diol;
[0046] (4) Phosphorus-containing diol, triethanolamine, 1,4-butanediol, deionized water, liquid paraffin and modified porous nano-titanium dioxide microspheres were mixed in a mass ratio of 1:0.15:1.4:0.2:0.65:1.3, stirred at 2000 r / min for 2 min, added with 0.7 times the mass of the phosphorus-containing diol melt-polymerized polyisocyanate, continued stirring for 10 s, added with 2.5 times the mass of the phosphorus-containing diol hydrogenated silicone oil and 0.015 times the mass of the phosphorus-containing diol chloroplatinic acid, continued stirring for 2 min, poured into a mold coated with dimethyl silicone oil, foamed at 25°C for 10 min, and allowed to stand at 70°C for 24 h to obtain an anti-aging sound insulation material.
[0047] Example 3
[0048] A method for preparing an anti-aging sound insulation material, the method for preparing an anti-aging sound insulation material comprising the following preparation steps:
[0049] (1) The polystyrene microsphere template emulsion and anhydrous ethanol were mixed at a mass ratio of 1:101, stirred at 85°C and 200 rpm for 25 minutes, tetrabutyl titanate was added at a mass of 0.2 times the mass of the polystyrene microsphere template emulsion, and the stirring was continued for 25 minutes. Ammonia water with a mass fraction of 28% and a mass fraction of 9 times the mass of the polystyrene microsphere template emulsion was added at a uniform speed within 5 hours, and the mixture was stirred for 1 hour and then centrifuged. The mixture was washed with deionized water for 5 times, dried at 65°C for 4 hours, and then ground for 10 minutes. The mixture was transferred into a muffle furnace and ablated at 550°C for 1 hour, and naturally cooled to room temperature to obtain porous nano-titanium dioxide microspheres;
[0050] (2) The porous nano-titanium dioxide microspheres and the ethanol solution with a mass fraction of 98% were mixed at a mass ratio of 1:17, ultrasonically dispersed for 35 minutes, hydroxymethyltriethoxysilane with a mass fraction of 4 times that of the porous nano-titanium dioxide microspheres was added, and ultrasonic dispersion was continued for 35 minutes. The temperature was raised to 65°C, stirred at 250 rpm for 2 hours, and then centrifuged. The solution was washed with anhydrous ethanol for 5 times and dried at 55°C for 47 hours to obtain pre-modified porous nano-titanium dioxide microspheres. The pre-modified porous nano-titanium dioxide microspheres, sodium hydride and N,N-dimethylformamide were mixed at a mass ratio of 1:0.07:11, and heated at 8°C and 200r / min for 30 minutes. pm, stirring for 10 min, adding 2-(5-chloro-2H-benzotriazole-2-yl)-6-(2-methyl-2-propyl)-4-vinylphenol in an amount of 1.8 times the mass of the pre-modified porous nano-titanium dioxide microspheres, continuing stirring for 2 h, naturally returning to room temperature, quenching with deionized water at 5°C, adding ethyl acetate in an amount of 40 times the mass of the pre-modified porous nano-titanium dioxide microspheres to extract the separated liquid, washing with a sodium chloride solution with a mass fraction of 27% and deionized water for 5 times respectively, and then drying with anhydrous sodium sulfate for 2 h, distilling under reduced pressure and purifying with a silica gel chromatography column to obtain modified porous nano-titanium dioxide microspheres;
[0051] (3) Allyl phosphine dichloride and n-hexane were mixed in a mass ratio of 1:4, and stirred at 30° C. and 200 rpm for 10 min to obtain a reaction solution; polyethylene glycol and tetrahydrofuran were mixed in a mass ratio of 1:3, and stirred at 30° C. and 500 rpm for 10 min, and the temperature was raised to 50° C., and the reaction solution was added at a uniform rate within 40 min while stirring, and the ratio of the molar amount of allyl phosphine dichloride in the reaction solution to the molar amount of hydroxyl groups in the polyethylene glycol was 1:4. After the addition, the mixture was allowed to stand for 1.5 h, and rotary evaporated to obtain a phosphorus-containing diol;
[0052] (4) Phosphorus-containing diol, triethanolamine, 1,4-butanediol, deionized water, liquid paraffin and modified porous nano-titanium dioxide microspheres were mixed in a mass ratio of 1:0.2:1.6:0.3:0.7:1.4, stirred at 2500 r / min for 1 min, added with 0.8 times the mass of phosphorus-containing diol melt-polymerized polyisocyanate, continued stirring for 5 s, added with 3 times the mass of phosphorus-containing diol hydrogenated silicone oil and 0.02 times the mass of phosphorus-containing diol chloroplatinic acid, continued stirring for 1 min, poured into a mold coated with dimethyl silicone oil, foamed at 30°C for 5 min, and allowed to stand at 75°C for 23 h to obtain an anti-aging sound insulation material.
[0053] Comparative Example 1
[0054] A method for preparing an anti-aging sound insulation material, the method for preparing an anti-aging sound insulation material comprising the following preparation steps:
[0055] (1) The porous nano-titanium dioxide microspheres and the ethanol solution with a mass fraction of 97.5% were mixed at a mass ratio of 1:16, ultrasonically dispersed for 30 minutes, hydroxymethyltriethoxysilane with a mass of 3 times that of the porous nano-titanium dioxide microspheres was added, and ultrasonication was continued for 30 minutes. The temperature was raised to 60°C, stirred at 175 rpm for 3 hours, and then centrifuged. The solution was washed with anhydrous ethanol for 4 times, and dried at 50°C for 48 hours to obtain pre-modified porous nano-titanium dioxide microspheres; the pre-modified porous nano-titanium dioxide microspheres, sodium hydride and N,N-dimethylformamide were mixed at a mass ratio of 1:0.06:10, and heated at 7°C and 150 rpm to obtain a pre-modified porous nano-titanium dioxide microsphere. Stir for 15 min, add 2-(5-chloro-2H-benzotriazole-2-yl)-6-(2-methyl-2-propyl)-4-vinylphenol in an amount of 1.7 times the mass of the pre-modified porous nano-titanium dioxide microspheres, continue stirring for 2.5 h, naturally return to room temperature, quench with deionized water at 4°C, add ethyl acetate in an amount of 35 times the mass of the pre-modified porous nano-titanium dioxide microspheres to extract the separated liquid, wash with a sodium chloride solution with a mass fraction of 26.5% and deionized water for 4 times respectively, and then dry with anhydrous sodium sulfate for 1.5 h, and purify with a silica gel chromatography column after reduced pressure distillation to obtain modified porous nano-titanium dioxide microspheres;
[0056] (2) allyl phosphine dichloride and n-hexane are mixed in a mass ratio of 1:3.5, and stirred at 25° C. and 150 rpm for 15 minutes to obtain a reaction solution; polyethylene glycol and tetrahydrofuran are mixed in a mass ratio of 1:2.5, and stirred at 25° C. and 450 rpm for 15 minutes, and the temperature is raised to 45° C., and the reaction solution is added at a uniform rate within 35 minutes while stirring, and the ratio of the molar amount of allyl phosphine dichloride in the reaction solution to the molar amount of hydroxyl groups in the polyethylene glycol is 1:4. After the addition, the mixture is allowed to stand for 1 hour, and rotary evaporated to obtain a phosphorus-containing diol;
[0057] (3) Phosphorus-containing diol, triethanolamine, 1,4-butanediol, deionized water, liquid paraffin and modified porous nano-titanium dioxide microspheres were mixed in a mass ratio of 1:0.15:1.4:0.2:0.65:1.3, stirred at 2000 r / min for 2 min, added with 0.7 times the mass of the phosphorus-containing diol melt-polymerized polyisocyanate, continued stirring for 10 s, added with 2.5 times the mass of the phosphorus-containing diol hydrogenated silicone oil and 0.015 times the mass of the phosphorus-containing diol chloroplatinic acid, continued stirring for 2 min, poured into a mold coated with dimethyl silicone oil, foamed at 25°C for 10 min, and allowed to stand at 70°C for 24 h to obtain an anti-aging sound insulation material.
[0058] Comparative Example 2
[0059] A method for preparing an anti-aging sound insulation material, the method for preparing an anti-aging sound insulation material comprising the following preparation steps:
[0060] (1) The polystyrene microsphere template emulsion and anhydrous ethanol were mixed at a mass ratio of 1:100, stirred at 80°C and 150 rpm for 30 min, tetrabutyl titanate was added at a mass of 0.15 times the mass of the polystyrene microsphere template emulsion, and the stirring was continued for 30 min. Ammonia water with a mass fraction of 27% and a mass fraction of 8 times the mass of the polystyrene microsphere template emulsion was added at a uniform speed within 4 h, and the mixture was stirred for 2 h and then centrifuged. The mixture was washed with deionized water for 4 times, dried at 60°C for 5 h, and then ground for 15 min. The mixture was transferred into a muffle furnace and ablated at 500°C for 2 h, and naturally cooled to room temperature to obtain porous nano-titanium dioxide microspheres;
[0061] (2) allyl phosphine dichloride and n-hexane are mixed in a mass ratio of 1:3.5, and stirred at 25° C. and 150 rpm for 15 minutes to obtain a reaction solution; polyethylene glycol and tetrahydrofuran are mixed in a mass ratio of 1:2.5, and stirred at 25° C. and 450 rpm for 15 minutes, and the temperature is raised to 45° C., and the reaction solution is added at a uniform rate within 35 minutes while stirring, and the ratio of the molar amount of allyl phosphine dichloride in the reaction solution to the molar amount of hydroxyl groups in the polyethylene glycol is 1:4. After the addition, the mixture is allowed to stand for 1 hour, and rotary evaporated to obtain a phosphorus-containing diol;
[0062] (3) Phosphorus-containing diol, triethanolamine, 1,4-butanediol, deionized water, liquid paraffin and porous nano-titanium dioxide microspheres were mixed in a mass ratio of 1:0.15:1.4:0.2:0.65:1.3, stirred at 2000 r / min for 2 min, added with 0.7 times the mass of the phosphorus-containing diol melt-polymerized polyisocyanate, continued stirring for 10 s, added with 2.5 times the mass of the phosphorus-containing diol hydrogenated silicone oil and 0.015 times the mass of the phosphorus-containing diol chloroplatinic acid, continued stirring for 2 min, poured into a mold coated with dimethyl silicone oil, foamed at 25°C for 10 min, and allowed to stand at 70°C for 24 h to obtain an anti-aging sound insulation material.
[0063] Comparative Example 3
[0064] A method for preparing an anti-aging sound insulation material, the method for preparing an anti-aging sound insulation material comprising the following preparation steps:
[0065] (1) The polystyrene microsphere template emulsion and anhydrous ethanol were mixed at a mass ratio of 1:100, stirred at 80°C and 150 rpm for 30 min, tetrabutyl titanate was added at a mass of 0.15 times the mass of the polystyrene microsphere template emulsion, and the stirring was continued for 30 min. Ammonia water with a mass fraction of 27% and a mass fraction of 8 times the mass of the polystyrene microsphere template emulsion was added at a uniform speed within 4 h, and the mixture was stirred for 2 h and then centrifuged. The mixture was washed with deionized water for 4 times, dried at 60°C for 5 h, and then ground for 15 min. The mixture was transferred into a muffle furnace and ablated at 500°C for 2 h, and naturally cooled to room temperature to obtain porous nano-titanium dioxide microspheres;
[0066] (2) The porous nano-titanium dioxide microspheres and the ethanol solution with a mass fraction of 97.5% were mixed at a mass ratio of 1:16, and ultrasonic dispersion was performed for 30 minutes. Hydroxymethyltriethoxysilane with a mass fraction of 3 times that of the porous nano-titanium dioxide microspheres was added, and ultrasonic dispersion was continued for 30 minutes. The temperature was raised to 60°C, stirred at 175 rpm for 3 hours, and then centrifuged. The solution was washed with anhydrous ethanol for 4 times, and dried at 50°C for 48 hours to obtain pre-modified porous nano-titanium dioxide microspheres. The pre-modified porous nano-titanium dioxide microspheres, sodium hydride and N,N-dimethylformamide were mixed at a mass ratio of 1:0.06:10, and heated at 7°C and 150 rpm for 48 hours. Stir for 15 min, add 2-(5-chloro-2H-benzotriazole-2-yl)-6-(2-methyl-2-propyl)-4-vinylphenol in an amount of 1.7 times the mass of the pre-modified porous nano-titanium dioxide microspheres, continue stirring for 2.5 h, naturally return to room temperature, quench with deionized water at 4°C, add ethyl acetate in an amount of 35 times the mass of the pre-modified porous nano-titanium dioxide microspheres to extract the separated liquid, wash with a sodium chloride solution with a mass fraction of 26.5% and deionized water for 4 times respectively, and then dry with anhydrous sodium sulfate for 1.5 h, and purify with a silica gel chromatography column after reduced pressure distillation to obtain modified porous nano-titanium dioxide microspheres;
[0067] (3) Polyethylene glycol, triethanolamine, 1,4-butanediol, deionized water, liquid paraffin and modified porous nano-titanium dioxide microspheres were mixed in a mass ratio of 1:0.15:1.4:0.2:0.65:1.3, stirred at 2000 r / min for 2 min, added with 0.7 times the mass of polyethylene glycol of molten polymer polyisocyanate, continued stirring for 10 s, added with 2.5 times the mass of polyethylene glycol of hydrogen-containing silicone oil and 0.015 times the mass of polyethylene glycol of chloroplatinic acid, continued stirring for 2 min, poured into a mold coated with dimethyl silicone oil, foamed at 25 ° C for 10 min, and allowed to stand at 70 ° C for 24 h to obtain an anti-aging sound insulation material.
[0068] Comparative Example 4
[0069] A method for preparing an anti-aging sound insulation material, the method for preparing an anti-aging sound insulation material comprising the following preparation steps:
[0070] (1) The polystyrene microsphere template emulsion and anhydrous ethanol were mixed at a mass ratio of 1:100, stirred at 80°C and 150 rpm for 30 min, tetrabutyl titanate was added at a mass of 0.15 times the mass of the polystyrene microsphere template emulsion, and the stirring was continued for 30 min. Ammonia water with a mass fraction of 27% and a mass fraction of 8 times the mass of the polystyrene microsphere template emulsion was added at a uniform speed within 4 h, and the mixture was stirred for 2 h and then centrifuged. The mixture was washed with deionized water for 4 times, dried at 60°C for 5 h, and then ground for 15 min. The mixture was transferred into a muffle furnace and ablated at 500°C for 2 h, and naturally cooled to room temperature to obtain porous nano-titanium dioxide microspheres;
[0071] (2) The porous nano-titanium dioxide microspheres and the ethanol solution with a mass fraction of 97.5% were mixed at a mass ratio of 1:16, and ultrasonic dispersion was performed for 30 minutes. Hydroxymethyltriethoxysilane with a mass fraction of 3 times that of the porous nano-titanium dioxide microspheres was added, and ultrasonic dispersion was continued for 30 minutes. The temperature was raised to 60°C, stirred at 175 rpm for 3 hours, and then centrifuged. The solution was washed with anhydrous ethanol for 4 times, and dried at 50°C for 48 hours to obtain pre-modified porous nano-titanium dioxide microspheres. The pre-modified porous nano-titanium dioxide microspheres, sodium hydride and N,N-dimethylformamide were mixed at a mass ratio of 1:0.06:10, and heated at 7°C and 150 rpm for 48 hours. Stir for 15 min, add 2-(5-chloro-2H-benzotriazole-2-yl)-6-(2-methyl-2-propyl)-4-vinylphenol in an amount of 1.7 times the mass of the pre-modified porous nano-titanium dioxide microspheres, continue stirring for 2.5 h, naturally return to room temperature, quench with deionized water at 4°C, add ethyl acetate in an amount of 35 times the mass of the pre-modified porous nano-titanium dioxide microspheres to extract the separated liquid, wash with a sodium chloride solution with a mass fraction of 26.5% and deionized water for 4 times respectively, and then dry with anhydrous sodium sulfate for 1.5 h, and purify with a silica gel chromatography column after reduced pressure distillation to obtain modified porous nano-titanium dioxide microspheres;
[0072] (3) Allyl phosphine dichloride and n-hexane are mixed in a mass ratio of 1:3.5, and stirred at 25° C. and 150 rpm for 15 minutes to obtain a reaction solution; polyethylene glycol and tetrahydrofuran are mixed in a mass ratio of 1:2.5, and stirred at 25° C. and 450 rpm for 15 minutes, and the temperature is raised to 45° C., and the reaction solution is added at a uniform rate within 35 minutes while stirring, and the ratio of the molar amount of allyl phosphine dichloride in the reaction solution to the molar amount of hydroxyl groups in the polyethylene glycol is 1:4. After the addition, the mixture is allowed to stand for 1 hour, and rotary evaporated to obtain a phosphorus-containing diol;
[0073] (4) Phosphorus-containing diol, triethanolamine, 1,4-butanediol, deionized water, liquid paraffin and modified porous nano-titanium dioxide microspheres were mixed in a mass ratio of 1:0.15:1.4:0.2:0.65:1.3, stirred at 2000 r / min for 2 min, added with molten polymer polyisocyanate in an amount of 0.7 times the mass of phosphorus-containing diol, continued stirring for 10 s, poured into a mold coated with dimethyl silicone oil, foamed at 25°C for 10 min, and allowed to stand at 70°C for 24 h to obtain an anti-aging sound insulation material.
[0074] Effect example
[0075] Table 1 below shows the analysis results of the anti-aging properties, flame retardant properties and sound insulation properties of the anti-aging sound insulation materials of Examples 1 to 3 of the present invention and Comparative Examples 1 to 4.
[0076] Table 1
[0077] Sound absorption coefficient Limiting oxygen index % Compression strength retention rate % Tensile strength retention rate % Example 1 0.85 28.7 91.2 81.4 Example 2 0.89 29.1 92.7 82.7 Example 3 0.84 28.6 91.9 81.6 Comparative Example 1 0.53 28.4 90.6 74.4 Comparative Example 2 0.85 27.2 76.3 63.2 Comparative Example 3 0.83 16.4 91.1 80.5 Comparative Example 4 0.81 18.3 89.8 78.9
[0078] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 1, it can be found that the anti-aging sound insulation material prepared by the present invention has good anti-aging performance, flame retardant performance and sound insulation performance.
[0079] By comparison, the sound absorption coefficient and tensile strength retention rate of Examples 1, 2 and 3 are higher than those of Comparative Example 1, indicating that the use of tetrabutyl titanate-coated polystyrene microsphere template to prepare porous nano-titanium dioxide microspheres with high porosity increases the specific surface area, enhances the scattering and diffraction of ultraviolet light and the reflection and scattering of sound waves, and improves the anti-aging and sound insulation properties of the anti-aging sound insulation material.
[0080] By comparison, the compression strength retention rate and tensile strength retention rate of Examples 1, 2 and 3 are higher than those of Comparative Example 2, which shows that the grafting of hydroxymethyltriethoxysilane and 2-(5-chloro-2H-benzotriazole-2-yl)-6-(2-methyl-2-propyl)-4-vinylphenol improves the dispersibility of the porous nano-titanium dioxide microspheres. At the same time, the introduction of benzotriazole structure and hindered phenol structure absorbs ultraviolet rays, captures active free radicals, and enhances the anti-aging performance of the anti-aging sound insulation material.
[0081] By comparison, the limiting oxygen index of Examples 1, 2, and 3 is higher than that of Comparative Example 3, which indicates that the introduction of phosphorus element by reacting allyl phosphine dichloride and polyethylene glycol can generate an inert carbon layer during combustion, isolate the combustion products, and improve the flame retardant properties of the anti-aging sound insulation material.
[0082] By comparison, the limiting oxygen index of Examples 1, 2, and 3 is higher than that of Comparative Example 4, which shows that the hydrogen-containing silicone oil can react with allyl phosphine dichloride and the double bonds on the modified porous nano-titanium dioxide microspheres to enhance the cross-linking effect between the materials and improve the stability. At the same time, the hydrogen-containing silicone oil can decompose at high temperature to produce a silicon oxide layer, forming a stable protective layer, thereby improving the flame retardant properties of the anti-aging sound insulation material.
[0083] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A method for preparing an anti-aging sound insulation material, characterized in that: The method comprises the following preparation steps: (1) The polystyrene microsphere template emulsion and anhydrous ethanol were mixed in a mass ratio of 1:(99~101), stirred at 75~85℃ and 100~200rpm for 25~35min, tetrabutyl titanate was added at a mass of 0.1~0.2 times the mass of the polystyrene microsphere template emulsion, and stirring was continued for 25~35min. Ammonia water with a mass fraction of 26~28% and a mass fraction of 7~9 times the mass of the polystyrene microsphere template emulsion was added at a uniform rate within 3~5h. Stirring was continued for 1~3h and then centrifuged. The mixture was washed with deionized water for 3~5 times, dried at 55~65℃ for 4~6h, and then ground for 10~20min. The mixture was transferred into a muffle furnace and ablated at 450~550℃ for 1~3h. The mixture was naturally cooled to room temperature to obtain porous nano-titanium dioxide microspheres. (2) The porous nano-titanium dioxide microspheres and the ethanol solution with a mass fraction of 97-98% were mixed at a mass ratio of 1:(15-17), ultrasonically dispersed for 25-35 minutes, hydroxymethyltriethoxysilane with a mass fraction of 2-4 times of the porous nano-titanium dioxide microspheres was added, and ultrasonic dispersion was continued for 25-35 minutes. The temperature was raised to 55-65°C, stirred at 150-250 rpm for 2-4 hours, and then centrifuged. The solution was washed with anhydrous ethanol for 3-5 times, and dried at 45-55°C for 47-49 hours to obtain pre-modified porous nano-titanium dioxide microspheres. The pre-modified porous nano-titanium dioxide microspheres, sodium hydride and N,N-dimethylformamide were mixed at a mass ratio of 1:(0.05-0.07):(9-11). , stirring at 6~8℃ and 100~200rpm for 10~20min, adding 2-(5-chloro-2H-benzotriazole-2-yl)-6-(2-methyl-2-propyl)-4-vinylphenol in an amount of 1.6~1.8 times the mass of the pre-modified porous nano-titanium dioxide microspheres, continuing stirring for 2~3h, naturally returning to room temperature, quenching with deionized water at 3~5℃, adding ethyl acetate in an amount of 30~40 times the mass of the pre-modified porous nano-titanium dioxide microspheres to extract the liquid, washing with a sodium chloride solution with a mass fraction of 26~27% and deionized water for 3~5 times respectively, and then drying with anhydrous sodium sulfate for 1~2h, and purifying with a silica gel chromatography column after reduced pressure distillation to obtain modified porous nano-titanium dioxide microspheres; (3) Allyl phosphine dichloride and n-hexane are mixed in a mass ratio of 1:(3-4), and stirred at 20-30°C and 100-200 rpm for 10-20 min to obtain a reaction solution; polyethylene glycol and tetrahydrofuran are mixed in a mass ratio of 1:(2-3), and stirred at 20-30°C and 400-500 rpm for 10-20 min, and the temperature is raised to 40-50°C. The reaction solution is added at a uniform rate while stirring within 30-40 min. The ratio of the molar amount of allyl phosphine dichloride in the reaction solution to the molar amount of hydroxyl groups in the polyethylene glycol is 1:
4. After the addition, the mixture is allowed to stand for 0.5-1.5 h, and then rotary evaporated to obtain a phosphorus-containing diol; (4) Phosphorus-containing diol, triethanolamine, 1,4-butanediol, deionized water, liquid paraffin and modified porous nano-titanium dioxide microspheres are mixed in a mass ratio of 1:(0.1-0.2):(1.2-1.6):(0.1-0.3):(0.6-0.7):(1.2-1.4), stirred at 1500-2500 r / min for 1-3 min, added with 0.6-0.8 times the mass of phosphorus-containing diol melt-polymerized polyisocyanate, continued stirring for 5-15 s, added with 2-3 times the mass of phosphorus-containing diol hydrogenated silicone oil and 0.01-0.02 times the mass of phosphorus-containing diol chloroplatinic acid, continued stirring for 1-3 min, poured into a mold coated with dimethyl silicone oil, foamed at 20-30°C for 5-15 min, and allowed to stand at 65-75°C for 23-25 h to obtain an anti-aging sound insulation material.
2. The method for preparing an anti-aging sound insulation material according to claim 1, characterized in that: The polystyrene microsphere template emulsion in step (1) is prepared by mixing polyvinyl pyrrolidone and deionized water in a mass ratio of 1:(48-52), stirring at 20-30° C. and 200-400 rpm for 25-35 min, adding styrene in an amount of 4-6 times the mass of polyvinyl pyrrolidone, continuing to stir for 10-20 min at 65-75° C. in a nitrogen atmosphere, adding potassium persulfate in an amount of 0.07-0.08 times the mass of polyvinyl pyrrolidone, and continuing to stir for 23-25 h.
3. The method for preparing an anti-aging sound insulation material according to claim 1, characterized in that: The melt polymerization polyisocyanate in step (4) is obtained by melting the polymerized polyisocyanate at 75-85° C. for 6-8 hours.
4. An anti-aging sound insulation material prepared according to the method for preparing an anti-aging sound insulation material according to any one of claims 1 to 3.
Citation Information
Patent Citations
Anti-aging textile fabric and preparation method thereof
CN112281492A
Polyurethane waterproof coating and preparation method thereof
CN117210116A